Potential Analysis of Aek Nauli Elephant Conservation in Preserving Biological Natural Resources - Bonaraja Purba; Regita Amelia; Debora Tarigas Marpaung (International Journal of Educational Technology Research, 2023)
Protecting endangered and endangered species by preserving their natural habitat is important today, one way is to do conservation. Wild animals need to be managed properly because protection of animals must be done because their populations are decreasing in the wild. One of the animals that must get attention for its almost extinct habitat is the elephant. It is known that the Sumatran elephant (Elephas maximus sumatranus) is on the verge of extinction. Elephants are a key species because of their impact on the environment. Keystone species are species that have a major impact on the environment and can affect ecosystems. The purpose of this research is to find out how the effect of elephant conservation in Aek Nauli Elephant Conservation on living natural resources as an effort to preserve living natural resources. Therefore Habitat conservation for key species has a positive impact on populations for other species because they depend on and share the same type of habitat for their survival.